The construction of confidence in a perceptual decision - Zylberberg, Ariel; Barttfeld, Pablo; Sigman, Mariano (Frontiers in Integrative Neuroscience, 2012)
Decision making involves the selection of one out of many possible courses of action. A decision may bear on other decisions, as when humans seek a second medical opinion before undergoing a risky surgical intervention. These ''meta-decisions'' are mediated by confidence judgments – the degree to which decision-makers consider that a choice is likely to be correct. We studied how subjective confidence is constructed from noisy sensory evidence. The psychophysical kernels used to convert sensory information into choice and confidence decisions were precisely reconstructed measuring the impact of small fluctuations in sensory input. This is shown in two independent experiments in which human participants made a decision about the direction of motion of a set of randomly moving dots, or compared the brightness of a group of fluctuating bars, followed by a confidence report. The results of both experiments converged to show that: i) confidence was influenced by evidence during a short window of time at the initial moments of the decision, and ii) confidence was influenced by evidence for the selected choice but was virtually blind to evidence for the non-selected choice. Our findings challenge classical models of subjective confidence – which posit that the difference of evidence in favor of each choice is the seed of the confidence signal.